Case series of endoscopic treatment of post-intubation tracheal stenosis - Salim Salloum, MD. MSc.; Michel Tawk, MD. MSc; Ralph Nehme, MD; Dima Siblani, MD; Youssef Haddad, MD (Respiratory Medicine Case Reports, 2022)
Introduction: Benign tracheal stenosis is a common problem encountered after tracheal intubation or tracheostomy. It can be managed by surgical or nonsurgical techniques. This case series describes the outcome of 11 cases of endobronchial treatment for complex tracheal stenoses. Methods: A retrospective study was carried out in two hospitals in Lebanon. Patients were contacted on a regular basis for 6 months and asked about the presence of dyspnea and its characteristics. Results: The most common presenting symptom was inspiratory stridor. Five patients (45.45%) were not satisfied after the bronchoscopic intervention. Six patients (54.55%) were satisfied with the outcome. All were initially treated with argon plasma coagulation and dilation. If any persistent symptoms were present, stenting was done. Three patients had a stent placement. Failure of stenting occurred with two patients. None of the satisfied patients had any early symptoms. Conclusion: Bronchoscopic interventions yielded acceptable results when treating complex stenoses. More data is still needed to guide physicians for better approaches. When confronting complex tracheal stenosis, a multidisciplinary approach between surgical and nonsurgical doctors is preferred to choose the best medical care.